2009
DOI: 10.1136/bjsm.2008.050799
|View full text |Cite
|
Sign up to set email alerts
|

The anticipatory regulation of performance: the physiological basis for pacing strategies and the development of a perception-based model for exercise performance

Abstract: During self-paced exercise, the exercise work rate is regulated by the brain based on the integration of numerous signals from various physiological systems. It has been proposed that the brain regulates the degree of muscle activation and thus exercise intensity specifically to prevent harmful physiological disturbances. It is presently proposed how the rating of perceived exertion (RPE) is generated as a result of the numerous afferent signals during exercise and serves as a mediator of any subsequent altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
461
6
43

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 422 publications
(552 citation statements)
references
References 42 publications
42
461
6
43
Order By: Relevance
“…This finding was supported by Billaut et al [45] who used a repeated sprint cycling protocol and also found no differences in RPE between trials where participants were not informed how many sprints they would be completing in comparison to an accurately informed trial. The finding of a lower accumulation of work over the ten, six second sprints in the unknown condition supports theory of selfpaced exercise [21] , where work-rate is expected to be set more conservatively. The inconsistency in the findings of RPE responses in open-loop exercise may be explained by differences in participant characteristics.…”
Section: Open-loop Exercisesupporting
confidence: 70%
See 4 more Smart Citations
“…This finding was supported by Billaut et al [45] who used a repeated sprint cycling protocol and also found no differences in RPE between trials where participants were not informed how many sprints they would be completing in comparison to an accurately informed trial. The finding of a lower accumulation of work over the ten, six second sprints in the unknown condition supports theory of selfpaced exercise [21] , where work-rate is expected to be set more conservatively. The inconsistency in the findings of RPE responses in open-loop exercise may be explained by differences in participant characteristics.…”
Section: Open-loop Exercisesupporting
confidence: 70%
“…Baden et al's study [46] found that in a 20-minute treadmill exercise bout at a fixed intensity of 75% of peak speed, oxygen uptake was lower in the latter half of a trial in which the duration was unknown compared to a trial where the duration was known. Therefore a greater running economy and more efficient performance due to the uncertainty of the exercise provide support for Tucker's [21] model. However, the mechanisms by which efficiency was enhanced are currently unknown as no differences in RPE, heart rate or stride frequency were found between the unknown and known conditions.…”
Section: Open-loop Exercisementioning
confidence: 91%
See 3 more Smart Citations